Reciprocity in Human Societies From Ancient Times to the Modern Welfare State - Kujala, Antti; Danielsbacka, Mirkka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Presenting new insights into reciprocity, this book combines Marcel Mauss's well-known gift theory with Barrington Moore's idea of mutual obligations linking rulers and the ruled. Teasing out the interrelatedness of these approaches, Reciprocity in Human Societies suggests that evolutionary psychology reveals a human tendency for reciprocity and collaboration, not only in a mutually cooperative way but also through increasing retributive moral emotions. The book discusses various historical societies and the different models of the current welfare state-Nordic (social democratic), conservative, and liberal- and the repercussions of the neoliberal policies of tax havens, tax cuts, and austerity with a cross-disciplinary approach that bridges evolutionary psychology, sociology, and social anthropology with history.
1. Introduction -- 2. Inca and Maya Reciprocity -- 3. The Indian Gift and Village Servants -- 4. Moral Obligations in Early Modern Japan -- 5. Gift Exchange and Reciprocity in the Nordic Countries -- 6. Reciprocity in the French Army in the First World War and in the Finnish Army in 1941-44 -- 7. The Modern Welfare State -- 8. Inequality in the United States and Other Industrialized Countries -- 9. Reciprocity Past and Present.
Keywords: Ethnology; Social sciences -- Philosophy; Welfare state; Psychobiology; Sociology; Social structure; Equality; Sociocultural Anthropology; Social Theory; Welfare; Biological Psychology; Sociological Theory; Social Structure